2016
DOI: 10.1111/infa.12135
|View full text |Cite
|
Sign up to set email alerts
|

Do Infants Recognize Engagement in Social Interactions? The Case of Face‐to‐Face Conversation

Abstract: a Trois-Rivi eresThis study explores 12-month-olds' understanding of face-to-face conversation, a key contextual structure associated with engagement in a social interaction. Using a violation-of-expectations paradigm, we habituated infants to a "face-to-face" conversation, and in a test phase compared their looking times between "back-to-back" (conceptually novel) and "face-toface" (conceptually familiar) conversations, while simultaneously manipulating perceptual familiarity in a 2 9 2 factorial design. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…This face-to-face effect has also been reported in previous studies that used either dynamic or static stimuli (Augusti et al, 2010; Handl et al, 2013; Gustafsson et al, 2016). Another aspect of our results, although not significant, was that the 1.5-year-old infants tended to show a higher looking frequency than the younger age groups.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This face-to-face effect has also been reported in previous studies that used either dynamic or static stimuli (Augusti et al, 2010; Handl et al, 2013; Gustafsson et al, 2016). Another aspect of our results, although not significant, was that the 1.5-year-old infants tended to show a higher looking frequency than the younger age groups.…”
Section: Discussionsupporting
confidence: 82%
“…It is important to note that the interaction phase in the current study did not include a turn-taking structure (especially conversation) as information, which contrasts with previous studies (Augusti et al, 2010; Gustafsson et al, 2016). Instead, we used silent movies and the models acted simultaneously.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…So far within the adult attachment research field, studies differentiating between attachment‐related and neutral situations, showed that the attachment‐related context can make a difference in attentional bias, selective attention and levels of empathy between secure and insecure individuals (Dewitte et al, 2007; Maleki, Mazaheri & Dehghani, 2013; Rashidi et al, 2016). As suggested by Gustafsson and colleagues (2016), after 12 months of age, infants may have enough experience to attend mostly to the interactions foreshadowing relevant outcomes to them, such as a caregiver taking a feeding bottle. Since such stimuli may affect infants’ expectations, we have added an attachment‐related context condition.…”
Section: Introductionmentioning
confidence: 99%